Democracy as an Elite Tool for Oppressing the Majority: A Case of Selected African Countries - Mohale Ernest Selelo; Magatane Tshwarelo Mashilo (Center for Risk Management & Sustainability and RSF Press, 2023)
This paper seeks to establish and investigate the incontrovertible scenarios that the people of Zimbabwe and Uganda experienced during the dawn of democracy. This paper argues that